2018
DOI: 10.1016/j.expneurol.2018.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Lithium modulates the muscarinic facilitation of synaptic plasticity and theta-gamma coupling in the hippocampal-prefrontal pathway

Abstract: Mood disorders are associated to functional unbalance in mesolimbic and frontal cortical circuits. As a commonly used mood stabilizer, lithium acts through multiple biochemical pathways, including those activated by muscarinic cholinergic receptors crucial for hippocampal-prefrontal communication. Therefore, here we investigated the effects of lithium on prefrontal cortex responses under cholinergic drive. Lithium-treated rats were anesthetized with urethane and implanted with a ventricular cannula for muscari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 96 publications
2
15
0
3
Order By: Relevance
“…On the other hand, a prior potentiation of AMPAr transmission by LTP induction 24 somehow produced a state of reduced sensitivity to MK-801 25 . Consistently, prior studies showed that allosteric modulation of AMPAr can prevent NMDAr antagonist-induced impairments 27,29,30 . It has been hypothesized that a prior AMPAr activation can produce depolarization of membrane potentials, relieving the Mg 2+ block of colocalized NMDAR and, consequently, attenuating NMDAr hypofunction 26,27 .…”
supporting
confidence: 76%
See 1 more Smart Citation
“…On the other hand, a prior potentiation of AMPAr transmission by LTP induction 24 somehow produced a state of reduced sensitivity to MK-801 25 . Consistently, prior studies showed that allosteric modulation of AMPAr can prevent NMDAr antagonist-induced impairments 27,29,30 . It has been hypothesized that a prior AMPAr activation can produce depolarization of membrane potentials, relieving the Mg 2+ block of colocalized NMDAR and, consequently, attenuating NMDAr hypofunction 26,27 .…”
supporting
confidence: 76%
“…Despite its limitations, the urethane anesthesia has been regarded as a valid model to test mechanistic hypotheses involving brain oscillations and synaptic plasticity in normal [28][29][30][31] and pathological situations 32,33 . Particularly relevant for this study, rodents under urethane anesthesia have been useful to examine which are the effects induced by NMDAr antagonists that are independent of the typical hyperlocomotion observed after treatment 18 .…”
mentioning
confidence: 99%
“…Cross-frequency coupling was estimated by the modulation index as described by Tort and adapted in previous work from our group 81,82 . Briefly, comodulation maps were constructed applying Hilbert transform to the signal filtered in bins of 0.5 Hz from 1 to 20 Hz on steps of 1 Hz for the phase modulating signal, while the amplitude modulated signal was filtered in bins of 1 Hz from 10 to 120 Hz on steps of 5 Hz.…”
Section: Phase-amplitude Couplingmentioning
confidence: 99%
“…Da ABL, o CPF recebe aferências monosinápticas glutamatérgicas, em específico no córtex pré-límbico, atingindo os dendritos de neurônios piramidais e interneurônios nas camadas II e V (MCDONALD, 1991(MCDONALD, , 1996MITRANO et al, 2010). No CPF, por sua vez, existem eferências glutamatérgicas partindo da camada II para interneurônios GABAérgicos da ABL, fechando a comunicação entre a ABL e o CPF (GABBOTT et al, 2005;HÜBNER et al, 2014;LITTLE e CARTER, 2013 (ESTEVES et al, 2017;GODSIL et al, 2013;RUGGIERO et al, , 2018 No biotério, os animais foram alojados em grupos de quatro em uma caixa de polipropileno (40 x 33 x 18 cm) contendo raspas de madeira (maravalha) sobre o assoalho.…”
Section: Introductionunclassified
“…Esta função usa o método de periodograma modificado por Welch e faz uma estimativa da magnitude quadrada de coerência do sistema. Com valores entre 0 e 1, a coerência espectral indica o quanto as oscilações de uma região correspondem à oscilação de outra região, e comumente é utilizada como um parâmetro para se avaliar a sincronia entre regiões(RUGGIERO et al, 2018). A magnitude da coerência quadrada é dada por:…”
unclassified